Radiology demand and capacity: A stochastic analysis based on care pathways - L. Sibanda; P. Engel-Hills; E. Hering; Shaofeng Liu (Cogent Business & Management, 2017)
The definition of (care) pathways, their advantages and disadvantages and the associated theories since the 1950s have been reported. Important in the definitions is that clinical care pathways are defined for a single examination process and that variances in clinical examination or clinical setting introduce variances in the clinical pathway. The objective of this study was to provide stochastic evidence necessary to establish a radiology care map that has “the right people, doing the right things, in the right order, at the right time, in the right place, with the right outcome”. Following a rigorous ethics approval process, data was collected from all consenting departments, radiographers (in their individual professional capacities) and a random sample of patients through document review, interview and observational research approaches. The outcome of the study supports blurring the scope of practice boundaries and timely execution of radiography examinations. However, there remains the need for further research to map care pathways for other radiology procedures and patients whose care is more variable and less standard.
Keywords: 650